2018
DOI: 10.20944/preprints201807.0079.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydrogen Sulfide-Releasing Fibrous Membranes: Potential Patches for Stimulating the Human Stem Cells Proliferation and Viability Under Oxidative Stress.

Abstract: The design of biomaterial platforms able to release bioactive molecules is mandatory in tissue repair and regenerative medicine. In this context, electrospinning is a user-friendly, versatile and low-cost technique, able to process different kinds of materials in micro- and nano-fibers with a large surface area-to-volume ratio for an optimal release of gaseous signalling molecules. Recently, the antioxidant and anti-inflammatory properties of the endogenous gasotramsmitter hydrogen sulfide (H2S), as well as it… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 59 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…It was demonstrated that H 2 S-releasing materials are able to enhance the proliferation of mesenchymal stem cells and cardiomyocytes (CMs). 52,53 To confirm the positive effects of H 2 Sreleasing hydrogel on treating MI, the expressions of inflammatory factors (TNF-α) and proangiogenic growth factors (VEGFA and Ang-1 mRNA) in the myocardium were determined by RT-PCR. As shown in Figure 8A, the ALG-CHO/ALG−TA−APTC/Geln/ADSCs hydrogel can dramatically reduce the expression of TNF-α and increase the expressions of VEGFA and Ang-1 compared with the MI group and other hydrogel groups (Figure 8B,C).…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%
“…It was demonstrated that H 2 S-releasing materials are able to enhance the proliferation of mesenchymal stem cells and cardiomyocytes (CMs). 52,53 To confirm the positive effects of H 2 Sreleasing hydrogel on treating MI, the expressions of inflammatory factors (TNF-α) and proangiogenic growth factors (VEGFA and Ang-1 mRNA) in the myocardium were determined by RT-PCR. As shown in Figure 8A, the ALG-CHO/ALG−TA−APTC/Geln/ADSCs hydrogel can dramatically reduce the expression of TNF-α and increase the expressions of VEGFA and Ang-1 compared with the MI group and other hydrogel groups (Figure 8B,C).…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%
“…In 2018, Melino and coworkers reported electrospun microfibrous polylactic acid (PLA) membranes containing garlic-derived organosulfur compounds fabricated using two different approaches (13). In the first approach, garlic oil-soluble extract (GaOS) was directly coated onto the electrospun microfibers (*700 nm in diameter) to yield GaOS-coated PLA fiber membranes (PFM+GaOS).…”
Section: Electrospun Fibersmentioning
confidence: 99%